The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ajog.2017.02.037
|View full text |Cite
|
Sign up to set email alerts
|

The maternal plasma proteome changes as a function of gestational age in normal pregnancy: a longitudinal study

Abstract: Objective Pregnancy is accompanied by dramatic physiologic changes in maternal plasma proteins. Characterization of the maternal plasma proteome in normal pregnancy is an essential step for understanding changes to predict pregnancy outcome. The objective of this study was to describe maternal plasma proteins that change in abundance with advancing gestational age, and determine biological processes that are perturbed in normal pregnancy. Materials and methods A longitudinal study included 43 normal pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
87
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 347 publications
(238 reference statements)
14
87
1
Order By: Relevance
“…However, 5 of the 8 placenta-specific proteins (placental growth factor, urokinase-type plasminogen activator, inhibin b A chain/activin A, MMP-12, and glypican 3) that showed significant changes across gestation in the current study paralleled the gestational changes reported by the previous study, although the latter 2 did not show significant changes after adjusting for multiple testing in our data set. The sixth protein (growth differentiation factor 15) was not part of the SOMAscan platform used by Romero and coworkers (47). For the 26 remaining proteins, the results from the 2 studies were in complete agreement.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, 5 of the 8 placenta-specific proteins (placental growth factor, urokinase-type plasminogen activator, inhibin b A chain/activin A, MMP-12, and glypican 3) that showed significant changes across gestation in the current study paralleled the gestational changes reported by the previous study, although the latter 2 did not show significant changes after adjusting for multiple testing in our data set. The sixth protein (growth differentiation factor 15) was not part of the SOMAscan platform used by Romero and coworkers (47). For the 26 remaining proteins, the results from the 2 studies were in complete agreement.…”
Section: Discussionmentioning
confidence: 86%
“…Changes across gestation in the maternal concentrations of a placentaderived protein are not critical for its usefulness as a biomarker or read-out of placental function; however, the pattern of change must be known because prediction models must allow for these changes. Romero and coworkers (47) used the SomaLogics platform to study maternal plasma proteomic profiles across gestation, and documented that there are marked gestational changes in Figure 2. Protein-protein interactions among proteins secreted by the placenta into the maternal circulation, analyzed with NetworkAnalyst.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, nearly every aspect of maternal physiology is impacted by pregnancy, leading to major changes in expression and function of genes, proteins, and organ systems. In the past, many of these changes have been studied in isolation, based on available technological capabilities . However, advanced technology now enables high‐dimensional study of genes, proteins, and other analytes.…”
Section: Expanding Systems Pharmacology In Pregnancy Beyond Pbpkmentioning
confidence: 99%
“…Romero et al . recently conducted a proteomics study that sampled plasma at 3–6 time points across gestation from 43 women with normal deliveries.…”
Section: Expanding Systems Pharmacology In Pregnancy Beyond Pbpkmentioning
confidence: 99%
See 1 more Smart Citation